PERLINDUNGAN HUKUM TERHADAP PEKERJA YANG MEMPEROLEH PEMUTUSAN HUBUNGAN KERJA DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Cagla Yasemin Goren; Ahmad Redi (Jurnal Hukum Adigama, 2021)
In Indonesia, the regulation on Employment is prescribed in Law Number 11 of 2003 concerning Employment. In 2020, the government enforced Law Number 11 of 2020 on Job Creation (Cipta Kerja). Since the law involves various sectors, the Job Creation Law is often dubbed as "One-Size-Fits-All" Law or Omnibus Law. With the stipulation of the Job Creation Law, there have been some changes to the Employment legislation. Job Creation law eliminates and changes part of the articles in Law No. 13 of 2003 on Employment. In this research, the author will discuss the role of Job Creation law in providing legal protection to the laborers/workers subject to the termination of work by the employers and study the new regulation in Job Creation Law on "Loss of Job Security." Loss of Job Security is a program run by the government through BPJS Ketenagakerjaan. The program aims to protect the terminated laborers/workers. The protection against the laborers/workers is vital because improving the laborers/workers welfare will ensure the preservation of harmony within the country.